TEKNIK PENGENDALIAN LALAT BUAH Bactrocera SP. (DIPTERA : TEPHRITIDAE) PADA PERTANAMAN CABAI MENGGUNAKAN PERANGKAP DENGAN ISYARAT KIMIA DAN VISUAL - Shahabuddin Shahabuddin (Universitas Tadulako, 2012)
Understanding and utilization of insect pest behavior are needed for developing an effectivecontrolling program. An experiment has been conducted in a chili plantation to determine how capturesof oriental fruit fly (Bactrocera sp.) were affected by combining olfactory and visual stimuli in traps.The study was performed by using a Completely Randomized Block design with 6 combinationtreatments of chemical (Melaleuca bracteata extract, MB) and visual (colour trap) cues and 3replications. The results showed that combination of MB and yellow colour of the traps wassignificantly more attractive to fruit flies than the other treatments and such treatments could reducethe infested level of the flies. Although chemical cues most likely has a stronger effect than visualcues on trapping the flies, this study suggest that an effective control of oriental fruit fly shouldinclude both visual and olfactory cues.Key words: Behavioral based control, fruit flies, trapping.